2014
DOI: 10.1371/journal.pone.0106386
|View full text |Cite
|
Sign up to set email alerts
|

Rice ORMDL Controls Sphingolipid Homeostasis Affecting Fertility Resulting from Abnormal Pollen Development

Abstract: The orosomucoids (ORM) are ER-resisdent polypeptides encoded by ORM and ORMDL (ORM-like) genes. In humans, ORMDL3 was reported as genetic risk factor associated to asthma. In yeast, ORM proteins act as negative regulators of sphingolipid synthesis. Sphingolipids are important molecules regulating several processes including stress responses and apoptosis. However, the function of ORM/ORMDL genes in plants has not yet been reported. Previously, we found that temperature sensitive genetic male sterility (TGMS) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 35 publications
1
13
1
Order By: Relevance
“…Suppression of LOC_Os07 g26940 ORMDL or all three rice ORMDLs lead to abnormal pollen development resulting in male sterility. In contrast with previous findings in yeasts and mammals, where decreased expression of ORMDLs leads to increased production of sphingolipids and ceramides, in tms2 sterile plants, where expression of LOC_Os07g26940 ORMDL is decreased, the ceramide levels are also decreased (66). It needs to be determined whether ORMDL-mediated regulation of sphingolipid biosynthesis could play a role in production of gametes, not only in plants, but also in other organisms.…”
Section: -Ketodihydrosphinganine Reductasecontrasting
confidence: 62%
“…Suppression of LOC_Os07 g26940 ORMDL or all three rice ORMDLs lead to abnormal pollen development resulting in male sterility. In contrast with previous findings in yeasts and mammals, where decreased expression of ORMDLs leads to increased production of sphingolipids and ceramides, in tms2 sterile plants, where expression of LOC_Os07g26940 ORMDL is decreased, the ceramide levels are also decreased (66). It needs to be determined whether ORMDL-mediated regulation of sphingolipid biosynthesis could play a role in production of gametes, not only in plants, but also in other organisms.…”
Section: -Ketodihydrosphinganine Reductasecontrasting
confidence: 62%
“…ORM proteins were found to be negative regulators of SPT in yeast [7] . In rice, RNAi against ORM-like genes also led to abnormal pollen development confirming the importance of sphingolipids for male fertility [16] .…”
Section: Introductionmentioning
confidence: 83%
“…OsAP65, a rice aspartic protease, was essential for male fertility and played a important role in pollen germination and pollen tube growth [ 79 ]. Chueasiri et al [ 80 ] quantified gene expression in anthers of temperature-sensitive rice plants grown in controlled growth rooms (26 °C and 32 °C) for fertile and sterile conditions, the results indicated that plant orosomucoids-like proteins influenced sphingolipid homeostasis, and deletion of this gene affected spikelet fertility resulting from abnormal pollen development. The transcription factor bHLH142 was identified as a pivotal role in tapetal programmed cell death and pollen development during early meiosis in rice [ 81 ].…”
Section: Discussionmentioning
confidence: 99%